Case Report: Staged surgical management in ESRD: off-pump CABG followed by renal transplantation to enhance graft survival - Özge Çetinarslan; Davit Saba (Frontiers in Cardiovascular Medicine)
Patients with end-stage renal disease face a significantly higher risk of cardiovascular diseases. For patients who are candidates for renal transplantation (RT), major surgeries such as coronary artery bypass grafting (CABG) are associated with cardiac complications as well as higher rates of post-operative complications, including the need for large amounts of blood transfusion, worsening kidney function, infection, and graft rejection. Studies have shown that blood transfusions can increase the risk of graft rejection due to immune system activation. Off-pump CABG (OPCAB), also known as beating heart surgery, is a technique in which a heart–lung machine is not used, and the heart continues to beat throughout the procedure. The main advantage of OPCAB surgery compared to on-pump CABG (ONCAB) is that it requires fewer blood product transfusions and has fewer renal, pulmonary, and hematological complications. This case series uniquely discusses two patients who underwent successful beating heart CABG without blood transfusion, followed by RT.